Effects of an online suicide crisis nursing education program on suicide prevention information literacy, attitudes toward suicide, and suicide prevention behaviors among general ward nurses in general hospitals - Ji Yeon Park; Hee Sook Kim (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: This study evaluated the effects of an online suicide crisis nursing education program on suicide prevention information literacy, attitudes toward suicide, and suicide prevention behaviors among general ward nurses.Methods: A quasi-experimental, non-equivalent control group pre-test–post-test design was used. Forty-seven nurses from two general hospitals were assigned to an experimental group (n=23) or a control group (n=24). The experimental group completed an eight-module online program over four weeks. Data were analyzed using the χ2 test, Fisher’s exact probability test, independent t-test, and Mann–Whitney U test.Results: Compared with the control group, the experimental group demonstrated significantly greater improvements in suicide prevention information literacy (p=.018) and suicide prevention behaviors (p